Models and Strategies when Effective use of Electronic Games in Teaching English Vocabulary - Alawaty, Afrah Haft; Abu Zahra, Somaya Suleiman (Journal of Curriculum and Teaching Methodology, 2023)
The intended aims of this study was to investigate the effectiveness of electronic educational games on direct academic achievement and its impact on learning English in the middle schools in Al-Taif; KSA. To achieve the study objectives, one-group quasi-experiment design based on pre- and post-tests exams was applied on the randomly selected sample consisting of 60 of middle school female students from the thirteenth prep school in Al-Taif. The researcher tools were: the electronic educational games program that was designed to teach English language and the academic achievement test of teaching English vocabularies; which was built by the researcher and applied after and before on the experimental sample of study. The study reached a number of results; the most important of which is the effectiveness of the proposed strategy (using electronic educational games) on direct academic achievement and learning English in the middle schools in Al-Taif; KSA. This was indicated via its role in the development of study sample students, after applying the program; in terms of reading comprehension skills, meaning remember skill, students flexibility and ability to create topics for discussion, enjoying with fun during class, feeling confident, understand meanings of words easily, knowing the meaning of words within the sentences and increasing their enthusiasm.
Keywords: Effective teaching strategies; electronic games; English language